Estimating infrastructure financing needs in the Asia-Pacific least developed countries, landlocked developing countries, and small island developing states - Candice Branchoux; Lin Fang; Yusuke Tateno (Economies, 2018)
To assist with the achievement of the Sustainable Development Goals by 2030, this paper develops a framework to estimate infrastructure financing needs of the Asia-Pacific least developed countries (LDCs), landlocked developing countries (LLDCs), and small island developing States (SIDS) by 2030. The framework takes into account the financing required to close existing infrastructure gaps, keep up with growing demands for new infrastructure, maintain existing infrastructure, and mitigate the vulnerability of infrastructure to climate-related risks. Based on a panel of 71 developing economies from 1990 to 2015 and the application of unit costs to the level of physical infrastructure stock projected to 2030, the required resources are estimated to amount to 8.1% of GDP per annum on weighted average, which exceeds current levels of infrastructure funding of 5-7% of GDP. The paper finds that a large proportion of financing needs in LDCs and SIDS arises from the current infrastructure shortages, particularly in the transport and energy sector, implying that provision of universal access to basic infrastructure services would require large outlays of resources. The results also suggest that LLDCs and some SIDS require over one-third of their spending to be allocated to maintenance and replacement of existing assets, while those in low-lying coastal areas face substantial long-run costs in improving infrastructure to mitigate climate change and protect them against loss and damages caused by extreme weather events. Meeting future infrastructure financing needs will require greater engagement of the private sector and other global and regional initiatives to ensure that sufficient resources can be raised for investment in infrastructure.
Keywords: O18; Q01; H54; 330; infrastructure financing; sustainable development; Asia-Pacific; developing countries with special needs